High-activity and high-stability supported monolithic catalyst as well as preparation method and application thereof

By using a supported monolithic catalyst composed of a first support with a three-dimensional connected foam structure and a uniformly coated second support, the Cu-Pd bimetallic catalytic active component is uniformly distributed on the surface of the second support, solving the problems of low activity and poor stability of the existing catalyst, achieving high activity and good stability, and significantly improving the reaction efficiency.

CN119549162APending Publication Date: 2025-03-04JINGDEZHEN CERAMIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411722441.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing supported monolithic catalysts have problems such as uneven distribution of active components, low catalytic activity and poor catalyst stability, resulting in catalyst wear, loss of active components and low reaction mass and heat transfer efficiency.

Method used

Using a supported monolithic catalyst composed of a first support (with a three-dimensional connected foam structure) and a second support (uniformly coated on the surface of the first support), the Cu-Pd bimetallic catalytically active component is uniformly distributed on the surface of the second support to form a catalyst with high dispersion and high specific surface area.

Benefits of technology

The high activity and good stability of the catalyst are achieved, the catalyst wear and loss of active components are avoided, the mass transfer and heat transfer efficiency of the reaction are improved, and the conversion and selectivity of the liquid phase oxidation reaction of benzyl alcohol are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549162A_ABST
    Figure CN119549162A_ABST
Patent Text Reader

Abstract

The invention discloses a high-activity and high-stability supported monolithic catalyst as well as a preparation method and application thereof. The supported monolithic catalyst is composed of a first carrier, a second carrier and Cu-Pd bimetallic catalytic active components, the first carrier has a three-dimensional communicated foam structure, and the second carrier is coated on the surface of the first carrier; the Cu-Pd bimetallic catalytic active component is supported on the second carrier, the content of Cu-Pd accounts for 0.01-10 wt% of the second carrier, and the molar ratio of Cu to Pd is 1.0: (0.1-1.5). The supported monolithic catalyst provided by the invention has high catalytic activity, can avoid wear of the catalyst and loss of active components, and has the advantages of good stability and long service life; meanwhile, the mass transfer and heat transfer processes of the reaction can be enhanced, and the catalyst is obviously superior to a traditional particle catalyst in the liquid-phase catalytic oxidation reaction of benzyl alcohol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalytic technology, and in particular to a high-activity and high-stability supported monolithic catalyst and a preparation method and application thereof. Background Art

[0002] The oxidation of alcohols to corresponding carbonyl compounds, especially the oxidation of benzyl alcohol to benzaldehyde, is a very important functional group conversion in organic synthesis. The catalytic performance of benzyl alcohol oxidation using non-precious metal catalysts is not as good as that of precious metal catalysts, and generally requires the participation of solvents and is carried out under medium-high temperature and high pressure conditions. Supported particle catalysts with precious metals such as Ru, Pd, Pt, and Au as active components are often used in liquid-phase oxidation reactions of benzyl alcohol. Precious metal catalysts have high catalytic activity and can achieve high target yields even under mild reaction conditions without solvents, but their cost is relatively high. Due to their synergistic electronic effect, bimetallic catalysts usually exhibit better catalytic reaction performance than single metal component catalysts. Therefore, the use of non-precious metals to partially replace precious metals to form bimetallic catalysts has always been a research hotspot in the field of heterogeneous catalysis.

[0003] The collision of the granular supported catalyst with the reactor components such as the stirring paddle, baffle, and the inner wall of the container during the reaction process easily causes the wear of the catalyst, resulting in the loss of catalytic active components, and there is also the problem of catalyst separation and recovery difficulties, which in turn affects the use efficiency and life of the catalyst. On the other hand, when the reaction substrate concentration or the catalyst dosage is large, the catalyst is easy to agglomerate, and the heat cannot be timely transferred in the strong exothermic reactions such as oxidation and hydrogenation, and it is easy to generate by-products and easily cause the catalyst to be deactivated and the life is reduced. With the continuous development of chemical process intensification technology and interdisciplinary integration, block structure materials (porous materials such as metals and ceramics) are promoted as carriers for supporting catalysts, thereby forming a new type of monolithic structured catalyst to achieve process intensification of catalytic reactions. This monolithic catalyst can avoid the wear of the catalyst, the loss of active components and the later filtering operation unit, and it is also helpful to strengthen the mass transfer and heat transfer process of the reaction, but the existing technology supported monolithic catalyst has problems such as uneven distribution of active components, low catalytic activity, and poor catalyst stability. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a high-activity and high-stability supported monolithic catalyst, which is mainly composed of a first carrier, a second carrier, and a Cu-Pd bimetallic catalytic active component, and has high catalytic activity while avoiding catalyst wear and loss of active components, thereby having the advantages of good stability and long service life. Another purpose of the present invention is to provide a preparation method and application of the above-mentioned high-activity and high-stability supported monolithic catalyst.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] The present invention provides a high-activity and high-stability supported monolithic catalyst, which consists of a first carrier, a second carrier, and a Cu-Pd bimetallic catalytic active component; the first carrier has a three-dimensionally interconnected foam structure, and the second carrier is coated on the surface of the first carrier; the Cu-Pd bimetallic catalytic active component is supported on the second carrier, wherein the Cu-Pd content accounts for 0.01 to 10 wt % of the second carrier, and the molar ratio of Cu:Pd is 1.0:0.1 to 1.5.

[0007] Furthermore, the first carrier of the present invention is A12O3 foam ceramic or SiC foam ceramic, and the number of foam meshes is 10 to 100PPI; the carrier raw material of the second carrier is one or a combination of two or more of alumina, activated carbon, silica, diatomaceous earth, aluminum silicate, and molecular sieve.

[0008] Another object of the present invention is achieved by the following technical solutions:

[0009] The method for preparing the above-mentioned high-activity and high-stability supported monolithic catalyst provided by the present invention comprises the following steps:

[0010] (1) washing and drying the first carrier to obtain a treated first carrier;

[0011] (2) dissolving the carrier raw material of the second carrier, the PVA binder, and the surfactant in deionized water in a mass ratio of the carrier raw material of the second carrier: the PVA binder: the surfactant = 15-25: 3-6: 0.5-2, and after ball milling, adjusting the pH value of the ball milling slurry to 3-6 to obtain a second carrier coating slurry with a solid content of 20-60%;

[0012] (3) dipping the treated first carrier into the second carrier coating slurry for 30 to 40 seconds, taking out and centrifuging, and then calcining at 400 to 600° C. for 1 to 6 hours in an air atmosphere to obtain a first carrier loaded with a second carrier coating;

[0013] (4) dissolving the copper source and sodium citrate in deionized water at a mass ratio of copper source: sodium citrate = 20-50: 5-10 to prepare copper colloid; dissolving the copper colloid, palladium source, pseudo-boehmite alumina sol, and polyethylene glycol-2000 in a PVA solution, and adjusting the pH value of the solution system to 3-6 to obtain a Cu and Pd precursor solution; at a mass ratio of copper colloid: palladium source: pseudo-boehmite alumina sol: polyethylene glycol-2000 = 10-30: 5-15: 5-10: 2-8;

[0014] (5) The first carrier loaded with the second carrier coating is immersed in the Cu and Pd precursor solution for 30 to 40 seconds. After being taken out, centrifuged and dried, it is first calcined in a muffle furnace at 350 to 450° C. in an air atmosphere for 0.5 to 2 hours. Then it is transferred to a quartz tube atmosphere furnace and reduced and calcined at 300 to 500° C. for 0.5 to 4 hours to obtain a high-activity and high-stability supported monolithic catalyst for liquid-phase oxidation of benzyl alcohol to prepare benzaldehyde.

[0015] Furthermore, in the step (1) of the preparation method of the present invention, the porosity of the first carrier is between 20% and 95%. In the steps (3) and (5), the centrifugal speed is 2000 to 6000 r / min, and the centrifugal time is 1 to 5 min; the thickness of the second carrier coating is 10 to 150 μm; and in the step (5), vacuum drying is performed at a temperature of 160 to 180° C. for 10 to 24 h.

[0016] Furthermore, the surfactant in the preparation method of the present invention is one or a combination of two or more of polyethylene glycol-2000, polysorbate, and polysorbate.

[0017] In the above scheme, the copper source in the preparation method of the present invention is one or a combination of two or more of copper chloride (CuCl2), copper sulfate (CuSO4), copper nitrate (Cu(NO3)2), copper acetate (Cu(CH3COO)2), copper oxalate (CuC2O4), copper fluoride (CuF2), and tetraamminecopper sulfate; the palladium source is one or a combination of two or more of palladium chloride (PdCl2), palladium nitrate (Pd(NO3)2), palladium sulfate (PdSO4), palladium acetate (Pd(C2H3O2)2), sodium tetrachloropalladate, and potassium tetrachloropalladate.

[0018] The application of the above-mentioned high-activity and high-stability supported monolithic catalyst of the present invention is used for preparing benzaldehyde by liquid-phase oxidation of benzyl alcohol, and the supported monolithic catalyst and the stirrer in the reactor are integrated and fixed on the mechanical stirring shaft. Cyclohexane, isopropanol, n-butanol or a combination of two or more thereof are used as the reaction solvent, H2O2 is used as the oxidant, and benzyl alcohol, the reaction solvent and the oxidant are added to the reactor in the form of a mixture for catalytic oxidation reaction. The conditions of the catalytic oxidation reaction are reaction pressure 1.2-2.0MPa, stirring rate 100-300rpm, reaction temperature 80-150°C, and reaction time 0.5-6h.

[0019] The present invention has the following beneficial effects:

[0020] (1) The supported monolithic catalyst of the present invention has a first carrier as a supporting skeleton of the catalyst and has a three-dimensional connected foam structure; the second carrier is evenly coated on the surface of the first carrier, and the Cu-Pd bimetallic catalytic active component nanoparticles are evenly distributed on the surface of the second carrier with high dispersibility. The Cu-Pd bimetallic catalytic active component nanoparticles are in the shape of popcorn balls, and the specific surface area of ​​the supported monolithic catalyst is 57.9 to 168.3 m 2 / g coating , pore volume is 0.093~0.216cm 3 / g foam .

[0021] (2) The Cu-Pd bimetallic catalytic active components of the supported monolithic catalyst of the present invention are evenly dispersed, and the second carrier coating and the catalytic active components are firmly supported. In the liquid-phase catalytic oxidation reaction of benzyl alcohol, it not only shows high catalytic activity, but also has excellent cycle stability. At the same time, the supported monolithic catalyst of the present invention is integrated with the agitator during use, and can avoid catalyst wear, active component loss and later filtering operation units in the liquid-phase catalytic reaction, and has the advantages of good stability and long service life, and helps to strengthen the mass transfer and heat transfer process of the reaction. In the liquid-phase catalytic oxidation reaction of benzyl alcohol, it is significantly better than the traditional particle catalyst (the conversion rate of benzyl alcohol is 90.5-99.8%, and the selectivity of benzaldehyde is 95.6-98.9%). BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The present invention will be further described in detail below with reference to the embodiments and accompanying drawings:

[0023] Figure 1 This is a SEM image of the high-activity and high-stability supported monolithic catalyst prepared in Example 1 of the present invention (a: magnification 100×; b: magnification 1000×). DETAILED DESCRIPTION

[0024] Embodiment 1:

[0025] The preparation method of the high-activity and high-stability supported monolithic catalyst of this embodiment comprises the following steps:

[0026] (1) ultrasonically cleaning alumina foam with a foam mesh number of 30 PPI in deionized water for three times, each time for 30 min, and drying in a forced air drying oven at 120° C. for 6 h to obtain a treated Al2O3 foam ceramic first carrier, the porosity of the first carrier being 70%;

[0027] (2) Dissolve the γ-Al2O3 powder, PVA binder and surfactant (polyethylene glycol-2000) in deionized water at a mass ratio of γ-Al2O3 powder: PVA binder (concentration of 1 wt%): surfactant = 15:3:1, ball mill the mixture on a planetary ball mill for 4 h, and then add nitric acid solution (8 M) to adjust the pH value of the ball milled slurry to 4, thereby obtaining a second carrier alumina coating slurry with a solid content of 45%;

[0028] (3) The treated Al2O3 foam ceramic first carrier was impregnated into the second carrier alumina coating slurry for 30 seconds, taken out and centrifuged (centrifugal speed was 5000 r / min, centrifugal time was 2 min), and then transferred to a muffle furnace and calcined at 400°C for 1 h in an air atmosphere to obtain the first carrier Al2O3 loaded with the second carrier coating γ-A12O3; the thickness of the second carrier coating was 100 μm;

[0029] (4) dissolving copper chloride and sodium citrate in deionized water at a mass ratio of copper chloride to sodium citrate = 50:5 to prepare copper colloid; dissolving the copper colloid, palladium chloride, pseudo-boehmite alumina sol, and polyethylene glycol-2000 in a PVA solution, and adding nitric acid to adjust the pH value of the solution system to 4 to obtain a Cu and Pd precursor solution; at a mass ratio of copper colloid: palladium chloride: pseudo-boehmite alumina sol: polyethylene glycol-2000 = 30:10:7:5;

[0030] (5) The first carrier A12O3 loaded with the second carrier coating γ-A12O3 was immersed in a Cu and Pd precursor solution for 30 seconds, taken out and centrifuged (centrifugal speed was 5000 r / min, centrifugal time was 2 min), and then vacuum dried at 160°C for 20 hours, first calcined in a muffle furnace at 400°C for 2 hours under air atmosphere, and then transferred to a quartz tube atmosphere furnace for reduction at 400°C for 2 hours to obtain a high-activity and high-stability supported monolithic catalyst (specific surface area of ​​65.9 m 2 / g coating , pore volume is 0.133cm 3 / g foam ).like Figure 1 As shown, the second carrier is evenly coated on the surface of the first carrier foam ribs.

[0031] The supported monolithic catalyst of this embodiment is used for the liquid phase oxidation of benzyl alcohol to prepare benzaldehyde. The operation process is as follows:

[0032] The supported monolithic catalyst prepared in this example was installed on a straight-blade paddle stirring shaft in a reactor with a volume of 1 L. 10 mL of reactant benzyl alcohol, 2 mL of oxidant H2O and 80 mL of reaction solvent isopropanol were added to the reactor in the form of a mixture, the reaction pressure was 1.5 MPa, the stirring speed was 300 r / min, the reaction temperature was 90°C, and the reaction time was 6 h. The conversion rate of benzyl alcohol was 95.3%, and the selectivity of benzaldehyde was 97.6%.

[0033] Embodiment 2:

[0034] The method for preparing the high-activity and high-stability supported monolithic catalyst in this embodiment is different from that in the first embodiment in that:

[0035] The added amounts of copper glue and palladium chloride are in the mass ratio of copper glue: palladium chloride = 30:15.

[0036] The supported monolithic catalyst of this embodiment is used for the liquid phase oxidation of benzyl alcohol to prepare benzaldehyde. The conversion rate of benzyl alcohol is 99.6%, and the selectivity of benzaldehyde is 98.3%.

[0037] Embodiment three:

[0038] The method for preparing the high-activity and high-stability supported monolithic catalyst in this embodiment is different from that in the first embodiment in that:

[0039] In step (3), the alloy is calcined at 500° C. for 5 h in an air atmosphere.

[0040] The supported monolithic catalyst of this embodiment is used for the liquid phase oxidation of benzyl alcohol to prepare benzaldehyde. The conversion rate of benzyl alcohol is 92.1%, and the selectivity of benzaldehyde is 96.6%.

[0041] Embodiment 4:

[0042] The method for preparing the high-activity and high-stability supported monolithic catalyst in this embodiment is different from that in the first embodiment in that:

[0043] The thickness of the second carrier coating in step (3) is 150 μm.

[0044] The supported monolithic catalyst of this embodiment is used for the liquid phase oxidation of benzyl alcohol to prepare benzaldehyde. The conversion rate of benzyl alcohol is 98.7%, and the selectivity of benzaldehyde is 97.5%.

[0045] Embodiment five:

[0046] The method for preparing the high-activity and high-stability supported monolithic catalyst in this embodiment is different from that in the second embodiment in that:

[0047] The first carrier is foamed silicon carbide.

[0048] The supported monolithic catalyst of this embodiment is used for the liquid phase oxidation of benzyl alcohol to prepare benzaldehyde. The conversion rate of benzyl alcohol is 97.5%, and the selectivity of benzaldehyde is 98.6%.

Claims

1. A high-activity and high-stability supported monolithic catalyst, characterized in that: The supported integral catalyst is composed of a first carrier, a second carrier, and a Cu-Pd bimetallic catalytic active component; the first carrier has a three-dimensionally interconnected foam structure, and the second carrier is coated on the surface of the first carrier; the Cu-Pd bimetallic catalytic active component is supported on the second carrier, wherein the Cu-Pd content accounts for 0.01 to 10 wt % of the second carrier, and the molar ratio of Cu:Pd is 1.0:0.1 to 1.

5.

2. The high-activity and high-stability supported monolithic catalyst according to claim 1, characterized in that: The first carrier is A12O3 foam ceramic or SiC foam ceramic, and the number of foam meshes is 10 to 100 PPI; the carrier raw material of the second carrier is one or a combination of two or more of alumina, activated carbon, silica, diatomaceous earth, aluminum silicate, and molecular sieve.

3. The method for preparing the high-activity and high-stability supported monolithic catalyst according to claim 1 or 2, characterized in that The following steps are involved: (1) washing and drying the first carrier to obtain a treated first carrier; (2) dissolving the carrier raw material of the second carrier, the PVA binder, and the surfactant in deionized water in a mass ratio of the carrier raw material of the second carrier: the PVA binder: the surfactant = 15-25: 3-6: 0.5-2, and after ball milling, adjusting the pH value of the ball milling slurry to 3-6 to obtain a second carrier coating slurry with a solid content of 20-60%; (3) dipping the treated first carrier into the second carrier coating slurry for 30 to 40 seconds, taking out and centrifuging, and then calcining at 400 to 600° C. for 1 to 6 hours in an air atmosphere to obtain a first carrier loaded with a second carrier coating; (4) dissolving the copper source and sodium citrate in deionized water at a mass ratio of copper source: sodium citrate = 20-50: 5-10 to prepare copper colloid; dissolving the copper colloid, palladium source, pseudo-boehmite alumina sol, and polyethylene glycol-2000 in a PVA solution, and adjusting the pH value of the solution system to 3-6 to obtain a Cu and Pd precursor solution; at a mass ratio of copper colloid: palladium source: pseudo-boehmite alumina sol: polyethylene glycol-2000 = 10-30: 5-15: 5-10: 2-8; (5) The first carrier loaded with the second carrier coating is immersed in the Cu and Pd precursor solution for 30 to 40 seconds. After being taken out, centrifuged and dried, it is first calcined in a muffle furnace at 350 to 450° C. in an air atmosphere for 0.5 to 2 hours. Then it is transferred to a quartz tube atmosphere furnace and reduced and calcined at 300 to 500° C. for 0.5 to 4 hours to obtain a high-activity and high-stability supported monolithic catalyst for liquid-phase oxidation of benzyl alcohol to prepare benzaldehyde.

4. The method for preparing a high-activity and high-stability supported monolithic catalyst according to claim 3, characterized in that: In the step (1), the porosity of the first carrier is between 20% and 95%.

5. The method for preparing a high-activity and high-stability supported monolithic catalyst according to claim 3, characterized in that: In the steps (3) and (5), the centrifugal speed is 2000-6000 r / min, and the centrifugal time is 1-5 min; the thickness of the second carrier coating is 10-150 μm; and in the step (5), vacuum drying is performed at a temperature of 160-180° C. for 10-24 h.

6. The method for preparing a high-activity and high-stability supported monolithic catalyst according to claim 3, characterized in that: The surfactant is one or a combination of two or more of polyethylene glycol-2000, polysorbate, and polysorbate.

7. The method for preparing a high-activity and high-stability supported monolithic catalyst according to claim 3, characterized in that: The copper source is one or a combination of two or more selected from the group consisting of copper chloride, copper sulfate, copper nitrate, copper acetate, copper oxalate, copper fluoride, and tetraammine copper sulfate; the palladium source is one or a combination of two or more selected from the group consisting of palladium chloride, palladium nitrate, palladium sulfate, palladium acetate, sodium tetrachloropalladate, and potassium tetrachloropalladate.

8. Use of the high-activity and high-stability supported monolithic catalyst according to claim 1 or 2 for preparing benzaldehyde by liquid-phase oxidation of benzyl alcohol, characterized in that: The supported monolithic catalyst and the stirrer in the reaction kettle are integrated into one body and fixed on a mechanical stirring shaft.

9. The use of the high-activity and high-stability supported monolithic catalyst according to claim 8, characterized in that: Cyclohexane, isopropanol, n-butanol or a combination of two or more thereof is used as a reaction solvent, H2O2 is used as an oxidant, and benzyl alcohol, the reaction solvent and the oxidant are added into the reactor in the form of a mixture to carry out a catalytic oxidation reaction.

10. The use of the high-activity and high-stability supported monolithic catalyst according to claim 9, characterized in that: The conditions of the catalytic oxidation reaction are reaction pressure of 1.2-2.0 MPa, stirring rate of 100-300 rpm, reaction temperature of 80-150° C., and reaction time of 0.5-6 h.